THE INFLUENCE OF WOMEN'S LEADERSHIP ON INNOVATION CAPABILITY AND PERCEIVED SUBORDINATE SUPPORT (A PRELIMINARY STUDY) - Lelly Christin; Yenli Megawati; Christian Haposan Pangaribuan; Glisina Dwinoor Rembulan (Sampoerna University, 2025)
This study investigates the relationships between women’s leadership, perceived subordinate support, and innovation capability within organizations in Jakarta, Indonesia. Despite a growing body of research on leadership and innovation, there remains a gap in understanding the specific contributions of women leaders and how subordinate support influences their effectiveness. Using a purposive sample of female leaders and employing a Structural Equation Modeling (SEM) approach with Partial Least Squares (PLS) analysis, the research tested three key hypotheses. The preliminary findings revealed a statistically significant positive relationship between women’s leadership and both innovation capability and perceived subordinate support. However, no direct, statistically significant relationship was found between perceived subordinate support and innovation capability. The results suggest that women leaders play a powerful and foundational role in an organization by fostering a supportive environment that, in turn, may indirectly influence innovation. This study contributes to the literature by highlighting the direct impact of women’s leadership on key organizational outcomes, while also serving as a preliminary basis for future research on the mediating role of subordinate support.